Host Feeding Patterns and Molecular Detection of Anaplasma and Ehrlichia in Ticks from Cattle Farms in Antioquia, Colombia (2025)
Ticks are important vectors of pathogens affecting both animals and humans, yet their role and associated bacteria remain understudied in Colombia, a country where livestock farming is economically significant. This study assessed the feeding sources of ticks collected from two cattle farms in Antioquia, Colombia, and molecularly detected Anaplasma and Ehrlichia species. Ticks were obtained from cattle and vegetation by manual and drag sampling, preserved, and identified. Feeding sources were determined using PCR-HRM targeting a vertebrate 16S rRNA gene fragment in 115 samples, with validation by Sanger sequencing. The analysis revealed feeding patterns from cattle (Bos taurus), horses (Equus caballus), and humans (Homo sapiens). Molecular screening by qPCR targeting the 23S rRNA gene identified eight positive samples: six for Anaplasma and one for Ehrlichia. Subsequent PCR and sequencing confirmed that all Anaplasma-positive samples corresponded to Anaplasma marginale, while the Ehrlichia-positive sample was classified as an uncultured Ehrlichia strain. Phylogenetic analysis of the rpoB gene supported these identifications, showing clustering with previously reported A. marginale sequences. Despite the low prevalence of infection, the detection of A. marginale and Ehrlichia spp. in Rhipicephalus microplus indicates epidemiological risks for cattle herds and potential zoonotic implications. These findings highlight the importance of integrated surveillance strategies that combine pathogen detection with host–vector interaction analysis to better understand the dynamics of tick-borne diseases in Colombian livestock systems.